A Multi-Layered Accountability Architecture (MLAA): A New Strategic Framework for Preventing Bribery in Indian Public Service Delivery - Mangla, Vinay (Digital Repository of Theses, 2026)
Bribery in India’s public service delivery persists despite decades of anti-corruption laws, vigilance institutions, and expanding digital reforms. The endurance of this problem highlights a deeper structural deficit: accountability mechanisms operate in isolation, leaving wide gaps where discretion flourishes and citizen trust erodes. A mixed-methods design was employed across selected Indian states representing diverse governance environments. Quantitative data from citizen surveys, service-delivery metrics, and complaint records were triangulated with qualitative interviews involving public officials, civil-society actors, and subject experts. The analysis identifies structural overlaps among watchdog agencies, procedural opacity, weak digital integration, low institutional responsiveness, and entrenched behavioural rationalisations as key drivers of bribery. Empirical testing indicates that isolated reforms-such as e-governance modules or internal vigilance units—reduce corruption only marginally when not supported by complementary layers of oversight and ethical reinforcement. The proposed MLAA framework introduces coordinated inter-agency protocols, transparent digital workflows, participatory feedback loops, and behavioural integrity mechanisms that operate simultaneously rather than sequentially. System-dynamics simulations suggest that strengthening one layer without reinforcing others yields short-lived gains, whereas integrated layers generate self-reinforcing improvements in transparency, efficiency, and citizen trust. Keywords Accountability, Bribery Prevention, Public Service Delivery, Governance Reform, Digital Transparency, Behavioural Integrity, India, MLAA Framework.